A splice variant of PGRP-LC required for expression of antimicrobial peptides in Anopheles gambiae - Lin, H; Zhang, L; Luna, C; Hoa, N; Zheng, L (2007)
Members of the peptidoglycan recognition protein (PGRP) family play essential roles in different manifestations of immune responses in insects. PGRP-LC, one of seven members of this family in the malaria vector Anopheles gambiae produced several spliced variants. Here we show that PGRP-LC, and not other members of the PGRP family nor the six members of the Gram-negative binding protein families, is required for the expression of antimicrobial peptide genes (such as CEC1 and GAMI) under the control of the Imd-Rel2 pathway in an A. gambiae cell line, 4a3A. PGRP-LC produces many splice variants that can be classified into three sub-groups (LC1, LC2 and LC3), based on the carboxyl terminal sequences. RNA interference against one LC1 sub-group resulted in dramatic reduction of CEC1 and GAM1. Over-expression of LC1a and to a lesser extent LC3a (a member of the LC1 and LC3 sub-group, respectively) in the 4a3A cell line enhances the expression of CEC1 and GAM1. These results demonstrate that the LC1-subgroup splice variants are essential for the expression of CEC1 and GAM1 in A. gambiae cell line. © Institute of Zoology, Chinese Academy of Sciences.